What do they need to know? Core skills for postgraduate development studies students. (15th July 2018) - Engel, Susan; Simpson Reeves, Laura
Abstract : Despite offerings at most universities, development studies in Australia does not have a professional body nor an academic association to prescribe core skills and standards, or to facilitate discussions about curriculum requirements and core competencies of graduates. This article analyses postgraduate coursework programmes focused on international and/or community development at 10 universities in Australia. It examines the faculty or school in which the programme is located, the core competencies the programmes aim to instil in graduates and how each programme is framed. In particular, it examines which skills have been defined as core requirements in line with the new Australian Qualifications Framework. The research found that, across Australia, development studies alternatively focuses students on critical thinking and understanding the history of 'development' or on teaching the practical skills (such as project and finance management) needed as development workers. We argue that the discipline needs to think more about core competencies and engage more actively in attempts to decolonise development studies teaching.